G. Călinescu la Universitate şi la Academia Română – precizări şi adăugiri – (I) - Pavel Țugui (Revista de Istorie și Teorie Literară)
The paper provides some new information about G. Calinescu’s university career, about his election as academician and his moving to the Institute of Literary History and Folklore of Bucharest. Pavel Ţugui reveals that Calinescu biography is still controversial, but he brings into the light documets that no one would contradict. Calinescu seems to have faced many difficulties to become professor at the University of Iasi. After one year, in 1945, he moved to the University of Bucharest. In 1949, he was sent away by the communist authorities, although he still was on the paylist of the Faculty of Letters and Philosophy, until 1952. In 1950 he was appointed director of the Institute of Literary History and Folklore of Bucharest, becoming employee of the Romanian Academy.